LIFE STYLE RELATED RISK FACTORS FOR CARDIOVASCULAR DISEASE AMONG PATIENTS AT A TEACHING HOSPITAL IN KARACHI - Qidwai, Waris; Mangi, Ali Raza; Bux, Rasool (Journal of Ayub Medical College Abbottabad, 2005)
Background: Cardiovascular disease is a leading cause for morbidity and mortality all over the world. It is important to study life style related, modifiable cardiovascular risk factors among patients, in order to devise preventive strategies. Methods: We surveyed family practice patients visiting the out-patient clinics of Aga Khan University Hospital, Karachi. The interview was questionnaire-based and recorded the demographic profile of the patients, in addition to information on life style related cardiovascular risk factors. The ethical requirements for the study were met. SPSS computer software was used for data management. Results: Fifty patients were surveyed and included 28 (56%) men and 22 (44%) women. Thirty seven (74%) respondents were married, nineteen (38%) had graduate education, Twenty five (50%) were in private service, and twelve (24%) were housewives. Twenty six (52%) respondents were overweight or obese. Butter, cream, margarine and red meat was consumed by 17(34%) and 32(64%) respondents respectively. White meat, fresh fruits and vegetables were consumed by 30 (60%), 29(58%) and 38(76%) respondents respectively. Oil from vegetable sources was used by 49(98%) respondents. Addition of table salt was found occasionally and always in 18(36%) and 09(18%) respondents respectively. Twenty seven (54%) respondents exercised at least twenty minutes, three times a week, while eleven (22%) were current smokers. Conclusions: Life style related modifiable risk factors are prevalent in patients reporting to our hospital. This offers an opportunity for preventive strategies, to prevent cardiovascular disease. Such surveys, followed by interventional strategies, are recommended to be followed by all Primary care facilities. Key-words: Cardiovascular disease-Risk factors-Life Style-Obesity